2008
DOI: 10.1007/s11845-008-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Day case shoulder surgery: satisfactory pain control without regional anaesthesia. A prospective analysis of a perioperative protocol

Abstract: Our study indicates a very high level of patient satisfaction and good pain relief without the use of regional anaesthesia for patients undergoing shoulder surgery as a day case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The results of this cohort group demonstrate that 90.4% were satisfied with their pain relief, even for open surgery and complex arthroscopic procedures. This level compares favourably with previously published results of shoulder surgery as a day‐case procedure, which report satisfaction in the range 80% to 85% [4,5]. Patient compliance in the present study was better than previous studies [5], with only two patients not following the postoperative regimen.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of this cohort group demonstrate that 90.4% were satisfied with their pain relief, even for open surgery and complex arthroscopic procedures. This level compares favourably with previously published results of shoulder surgery as a day‐case procedure, which report satisfaction in the range 80% to 85% [4,5]. Patient compliance in the present study was better than previous studies [5], with only two patients not following the postoperative regimen.…”
Section: Discussionsupporting
confidence: 85%
“…This level compares favourably with previously published results of shoulder surgery as a day‐case procedure, which report satisfaction in the range 80% to 85% [4,5]. Patient compliance in the present study was better than previous studies [5], with only two patients not following the postoperative regimen. The reasons for this are likely to be a combination of surgical and anaesthetic factors, as well as thorough patient education.…”
Section: Discussionsupporting
confidence: 85%
“…Hadzic et al demonstrated in a clinical trial that interscalene block for outpatient rotator cuff surgery provides several same-day recovery advantages over general anaesthesia [7]. Other studies have explored the alternatives: subacromial bursal block for subacromial decompressions [2] or combined subacromial and glenohumeral block for more complex procedures [3].…”
Section: Discussionmentioning
confidence: 99%
“…They stated that analgesia was inadequate after the block had worn off; and further commented that even if the patients were not daycases the block would have worn off on discharge the following day. Subsequent studies have explored the alternatives: subacromial bursal block for subacromial decompressions [2] or combined subacromial and glenohumeral block for more complex procedures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder arthroscopy is an increasingly popular method for treating ailments of the shoulder joint (Daruwalla et al, 2009). Complication rate has been reported at between 4.6% and 10.6% (Marecek and Saltzman, 2010;Rains et al, 2011).…”
Section: Introductionmentioning
confidence: 99%